2020
DOI: 10.4314/ejhs.v30i6.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of High Blood Pressure among Adults in Banyuwangi Coastal Communities, Indonesia

Abstract: BACKGROUND: Hypertension is a disease that still a problem in the world. Hypertension is a risk factor for heart disease and stroke mortality. Economic development and an emphasis on coastal tourism may have an impact on public health conditions, such as hypertension. This study aimed to determine risk factors related to hypertension among adults in coastal communities in Indonesia.METHODS: This was a cross-sectional study of 123 respondents between the age of 18-59 years old selected by cluster sampling. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…Age is a factor in the high incidence of hypertension, but not gender (Astutik et al, 2020). The age variable cannot be changed, and it is quite difficult to change from the socioeconomic status variable in the near future.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Age is a factor in the high incidence of hypertension, but not gender (Astutik et al, 2020). The age variable cannot be changed, and it is quite difficult to change from the socioeconomic status variable in the near future.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Hal ini disebabkan perempuan lebih sensitif terhadap hal-hal yang bersifat tantangan dan ancaman. (14) Bersamaan dengan penelitian yang diadakan bulan Mei hingga Juli 2022, mahasiswa angkatan 2021 berada pada semester (15) Berdasarkan penelitian terdahulu, tingkat kecemasan sedang atau berat secara signifikan dikaitkan dengan risiko nokturia setidaknya dua kali per malam. (16) Hal ini juga diperkuat oleh sebuah systematic review oleh Bliwise (5) , yang berfokus pada hubungan antara nokturia dan depresi/ kecemasan mengungkapkan bahwa depresi dan nokturia sering berdampingan secara bersamaan.…”
Section: Pembahasanunclassified
“…The results of the analysis of priority problems found that hypertension becomes the second priority to be tackled. Hypertension has been considered a major problem and a significant contributor to morbidity and mortality in Indonesia (Astutik et al, 2020;Peltzer & Pengpid, 2018) and all over the world(van Kleef and Spiering, 2017). The main cause of hypertension-related concerns is associated with compliance with antihypertensive medication.…”
Section: Each Month All-yearmentioning
confidence: 99%